القيمة الزمنية للنقود كأساس لعملية خصم التدفقات النقدية في الاقتصاد الإسلامي - د. رحماني, موسى; الغالي, أ. بن إبراهيم (Recherches économiques et managériales, 2012)
القيمة الزمنية للنقود هي حجر الزاوية في التمويل الحديث، إذ أصبحت المحرك الرئيسي للعمليات المالية والاقتصادية في مجالات شتى، وكذا اتخذت مبررا لعدة معاملات سواء في النظام الاقتصادي التقليدي أو الإسلامي، وذلك بغض النظر عن مشروعيتها أو عدمها . ويعد فهم القيمة الزمنية للنقود أمر أساسي لتحقيق النجاح المالي، والذي  يسمح بتقدير القيمة المحتملة من التدفقات النقدية مستقبلا، مما يوجب مراعاتها عند اتخاذ القرارات الاستثمارية والمالية في أي مشروع.    وعلى هذا الأساس أتت هذه الدراسة لتسلط الضوء على مفهوم أو ضرورة استخدام الزمن كعامل اقتصادي للمفاضلة بين المشروعات في الاقتصاد الإسلامي من خلال عملية خصم التدفقات النقدية المتولدة عن المشروعات الاستثمارية Abstract :    Time value of money is the cornerstone of modern finance, it has become the main driver of financial operations and economic development in various fields, as well as an excuse to have taken a number of transactions in the economic system, whether conventional or Islamic, and regardless of the legitimacy or lack thereof.  Understanding the time value of money is key to achieving financial success, which allows assessment of the potential value of future cash flows, which requires be taken into account when making investment decisions and financial in any project.   And on this basis of this study came to shed light on the concept or the need to use time as an economic factor for the trade-off between projects in the Islamic economy through the process of discounted cash flow generated by investment projects.